Predictors of survival in patients with disease recurrence after radical nephroureterectomy. (June 2014) - Kluth, Luis A.; Xylinas, Evanguelos; Kent, Matthew; Hagiwara, Masayuki; Kikuchi, Eiji; Ikeda, Masaomi; Matsumoto, Kazumasa; Dalpiaz, Orietta; Zigeuner, Richard; Aziz, Atiqullah; Fritsche, Hans‐Martin; Deliere, Amanda; et al.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the prognostic value of the Bajorin criteria in a multi‐institutional cohort of patients with disease recurrence after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). To investigate whether clinical, pathological and/or biological factors at time of disease recurrence are also associated with cancer‐specific outcomes in these patients. Patients and Methods We identified 242 patients with disease recurrence after RNU for UTUC from 11 centres. With regard to the Bajorin criteria, patients were categorized into three groups based on two risk factors: Karnofsky performance status <80% and the presence of visceral metastasis. Assessed variables included pathological characteristics, time to disease recurrence, age‐adjusted Charlson comorbidity index (ACCI), American Society of Anesthesiologists (ASA) score, and laboratory tests at time of disease recurrence. Results Overall, 185 patients died from their disease; the median survival was 9 months. The survival rates at 1 year were 53, 33, and 39% for patients with no (n = 18), one (n = 109) and two (n = 115) risk factors, respectively, with no significant difference between the groups. In univariable analyses, higher pT‐stage, tumour necrosis, non‐administered salvage chemotherapy, higher ACCI score, higher ASA score, lower albumin level and higher white blood cell count were significantly associated with a shorter time to cancer‐specific mortality. Conclusions We confirmed the poor yet variable outcomes of patients with disease recurrence after RNU. While the Bajorin criteria seem to have limited prognostic value in this specific cohort, we found several other clinical variables to be associated with worse cancer‐specific mortality. If validated, these factors should be taken into consideration for clinical trial design.